(untitled) - Blij, Harm J. De (New York, 1997)
This market-leading textbook has undergone a significant change: the overall organization has shifted from developed/underdeveloped countries to a more practical format which focuses on the enormous regional and social disparities in individual countries within the realm. The text has been streamlined and the chapters are organized into two distinct parts: Defining the Realm (physical, historical, and cultural background) and Regions of the Realm (more specific descriptions of each region). Contains increased emphasis on urban geography, reflected in a new segment entitled Among the Realm's Great Cities. As in previous editions, this one includes outstanding illustrative materials and the most up-to-date nomenclature and maps
Keywords: Geography,Địa lý